2014
DOI: 10.1016/j.schres.2014.06.039
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the factors that regulate muscarinic receptor expression in schizophrenia

Abstract: We previously identified a group of subjects with schizophrenia who, on average, have a 75% decrease in cholinergic receptor, muscarinic 1 (CHRM1) in Brodmann's area (BA) 9. To extend this finding, we determined i) if the decrease in CHRM1 was present in another functionally related CNS region (BA6), ii) whether the marked decrease in CHRM1 was accompanied by changes in levels of other CHRMs and iii) potential factors responsible for the decreased CHRM1 expression. We measured CHRM1 and CHRM3 using in situ rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“… 20 We have shown that it is possible to distinguish a subset of individuals within the disorder based on a marked loss of cortical muscarinic receptor binding; we have termed this subset as muscarinic receptor deficit schizophrenia (MRDS). Subjects with MRDS have been shown to have a widespread loss of cortical muscarinic receptors 21 , 22 similar to what was reported in some individuals with the disorder in a neuroimaging study of muscarinic receptors in schizophrenia. 23 Recently we have reported that subjects with MRDS also have decreased radioligand binding to striatal muscarinic receptors and higher levels of post-synaptic density protein 95, 24 showing changes in the molecular cytoarchitecture of the CNS in subjects with MRDS extends beyond the cortex.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“… 20 We have shown that it is possible to distinguish a subset of individuals within the disorder based on a marked loss of cortical muscarinic receptor binding; we have termed this subset as muscarinic receptor deficit schizophrenia (MRDS). Subjects with MRDS have been shown to have a widespread loss of cortical muscarinic receptors 21 , 22 similar to what was reported in some individuals with the disorder in a neuroimaging study of muscarinic receptors in schizophrenia. 23 Recently we have reported that subjects with MRDS also have decreased radioligand binding to striatal muscarinic receptors and higher levels of post-synaptic density protein 95, 24 showing changes in the molecular cytoarchitecture of the CNS in subjects with MRDS extends beyond the cortex.…”
Section: Introductionsupporting
confidence: 66%
“…We have previously reported that subjects with MRDS have been shown to have a widespread loss of cortical muscarinic receptors, 21 , 22 have disruptions in muscarinic M1 receptor signaling, 48 have a distinct pattern of muscarinic M1 receptor gene promoter methylation and higher levels of a microRNA that acts to reduce receptor expression, 49 and have a reduced response to a muscarinic M1-receptor-positive allosteric modulator. 50 In addition, we have reported that subjects with MRDS also have decreased radioligand binding to striatal muscarinic receptors and higher levels of post-synaptic density protein 95, 24 showing changes in the molecular cytoarchitecture of the CNS in subjects with MRDS extends beyond the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to allow us to better understand the potential impact of differing methods used for [ 3 H]NMS and [ 3 H]pirenzepine binding, we investigated whether the binding of these radioligands was ion dependent. Our studies were completed using Brodmann's area (BA) 6 because we confirmed that the marked decrease in [ 3 H]pirenzepine binding in subjects with MRDS, which was first identified in BA 9, was detectable in BA 6 (Seo et al, 2014) and because we had shown that this region of the cortex had decreased levels of neuregulin 1 (NRG1) (Barakat et al, 2010). As changes in NRG1 gene sequence has been associated with an increased risk of schizophrenia (Stefansson et al, 2002), we postulated molecular changes in BA 6 may reflect the impact of a biology dictated by an increased genetic predisposition for the disorder.…”
Section: Introductionsupporting
confidence: 59%
“…Following approval from the Tissue Access Committee of the Victorian Brain Bank Network, tissue was obtained from BA 6 (a cortical region that includes the anterior part of the paracentral lobule and the adjacent superior gyrus, the dorsal bank of the callosomarginal sulcus (minus its posterior third), and the bases of superior and middle frontal gyrus and pre-central gyrus not included in BA 4 (Garey, 1994)) from five subjects for methodological optimization. In addition, tissue was obtained from BA 6 from 40 subjects with schizophrenia and 20 age/sex-matched controls (demographics summarized in Table 1, complete detail in Supplementary Table 1) who had essentially been used in a previous study of [ 3 H]pirenzepine binding in that cortical region (Seo et al, 2014). The subjects with schizophrenia comprised 20 MRDS and 20 non-MRDS cases; the 20 subjects with MRDS were selected from the cases that we have previously shown separated into a subgroup within the syndrome of schizophrenia because of a marked loss of [ 3 H]pirenzepine binding in BA 9 ).…”
Section: Tissue Collection Diagnostic Validation and Membrane Prepamentioning
confidence: 99%
See 1 more Smart Citation